Management motives, monitoring mechanisms and political connections: critical factors influencing accounting misstatements of Malaysian Public Listed Companies (PLCs) / Alfiatul Rohmah Mohamed Hussain - Mohamed Hussain, Alfiatul Rohmah (2019)
This study investigates the factors that lead to the occurrence of accounting misstatements. Specifically, this study examines the effect of financial and non-financial measures management motives, as well as the internal and external governance of monitoring mechanisms and political connections on the occurrence of accounting misstatements in Malaysia. The financial measures is proxied by financial distress, market-related incentive, stock-option based compensation, related party transactions and earnings management, while non-financial measures is proxied by abnormal change in the number of employees, existence of founder on the firm’s board and managerial ownership. The internal governance is proxied by board effectiveness, family ownership, whereas external governance is proxied by audit quality and foreign ownership. In order to see the impact of management motives, monitoring mechanisms and political connection on the occurrence of accounting misstatements, 194 non-financial firms listed on the Main Market of Bursa Malaysia over the period 2005-2013 were selected, with complete data for management motives, monitoring mechanisms and political connection variables. The study uses cross-sectional logistic regression model to analyse the relationship between various factors of financial statement restatements and the occurrence of accounting misstatements. The result from multivariate analysis is validated using the bootstrap approach. From the regression analysis conducted, the study finds that the corporate environment most likely to lead to misstatement is characterized by factors that focus on the adoption of stock option-based compensation, lower audit quality and with the presence of political connections. Interestingly, the study finds that foreign investors effectively monitor the politically connected firms given the evidence that there is a negative and significant association between the interactions of foreign ownership with political connection, and the occurrence of misstatements. Using multinomial logistic regression in the additional analyses, this study finds evidence that financial distress, earnings management through accounts receivables and higher managerial ownership lead to revenue related restatement. The absence of the founder on the firm’s board, lower foreign ownership and high political connection lead to expense related restatement. The adoption of stock option-based compensation, poor board effectiveness and audit quality, and high foreign ownership lead to other types of restatements. Yet, the study finds that earnings-to-price, related party transactions and abnormal change in the number of employees are not significant determinants of accounting misstatements in Malaysia. Overall, this study contributes to the extant literature by evidencing that the occurrences of accounting misstatements depend on the culture of an organization that tends to report favourable earnings, while taking into account the unique institutional context of an Asian country. Finally, it is hoped that the study will benefit and help the regulatory bodies in improving the rules and laws, the firms in formulating the best corporate strategies and improving their system controls, and the users of the financial information, especially the investors in making their financial decisions.